Célula de comutação aplicada a um conversor Boost de alto ganho - Silva, Ranoyca Nayana Alencar Leão e (2009)
This work presents the qualitative and quantitative analysis, the control circuitry, simulation and experimental results of a soft switching cell applied on a high gain boost converter. The PID compensator is implemented digitally on a microcontroller PIC 16F877A. It assures that 180 volts of output does not changes with load variations. The soft switching cells applied on the main switches of the converter causes low switching losses. The main features proposed to this system are: common source terminal to all the switches, ZVS commuting on the main switches, ZCS commuting on the auxiliaries, low voltage switching stress, balanced voltage on the output capacitors, the presence of a magnetic coupling cell, which allows an even higher gain, and the magnetic components operating with the double of switching frequency. A prototype of 500W was built to validate the work principles of the proposed system.